In vitro model for investigating aerosol dispersion in a simulated COVID-19 patient during high-flow nasal cannula treatment - McGrath, James A.; O’Sullivan, Andrew; Joyce, Mary; Byrne, Miriam A.; Li, Jie; Fink, James B.; MacLoughlin, Ronan (Frontiers in Medicine, 2022)
The use of high-flow nasal cannula in the treatment of COVID-19 infected patients has proven to be a valuable treatment option to improve oxygenation. Early in the pandemic, there were concerns for the degree of risk of disease transmission to health care workers utilising these treatments that are considered aerosol generating procedures. This study developed an in vitro model to examine the release of simulated patient-derived bioaerosol with and without high-flow nasal cannula at gas flow rates of 30 and 50 L/min. Aerosol dispersion was evaluated at 30 and 90 cm distances. Reduction of transmission risk was assessed using a surgical facemask on the manikin. Results indicated that the use of a facemask facilitated a 94-95% reduction in exhaled aerosol concentration at 30 cm and 22 – 60% reduction for 90 cm distance across both gas flow rates. This bench study confirms that this in vitro model can be used as a tool to assess the risk of disease transmission during aerosol generating procedures in a simulated patient and to test factors to mitigate the risk.